Dietary Assessment of energy drinks from the standpoint of the athletes in the city of Baghdad - study Astpianih (Journal of the College of Education for Women, 2019)
The energy aimed at examining the mode of energy drinks consumption among athletes inBaghdad and assessing their drinks were spread greatly among the athletes and students. Thisstudy impression toward such drinks. The study sample comprised of 102 mal athletes agedbetween 19-27 years and selected randomly .The obtained results showed that football wasmost practiced among the test samples at 40.54% based on twice daily .The athletesconsumed one can each day at 41.18% .As the data on energy drinks was supplied fromfriends .The prefared period for drinking was before or during exercise .The athletes thoughtthat there products can provide energy ,vitamins ,tell ale materials ,does not affectappetite.The most favorate drink was Tigger to low price and dosired taste.